Investigating GoPro and its diffusion of innovations - Hambrick, Marion E. (London : SAGE Publications: SAGE Business Cases Originals, 2019)
GoPro became a public company in 2014 to much fanfare, as it was rated as a top technology initial public offering for the year. Company founder and CEO Nick Woodman and his leadership team have faced a series of challenges since the initial public offering. In 2018, the GoPro stock price decreased to less than USD 10 per share after reaching an all-time maximum of nearly USD 100 per share. The company discontinued its Karma drone line, noting a desire to focus on cameras, its core product. The fourth corporate restructuring, in early 2018, drove the GoPro headcount below 1,000 employees. Yet Woodman seemed confident in the future of the company. On the second quarter 2018 earnings call, he highlighted positive news such as year-to-date camera sales similar to those reported during the first half of 2017. The company also reported lower operating expenses stemming from the restructuring. As a result, Woodman forecasted that GoPro would generate profits in the second half of 2018 and continue this profitability through 2019. Industry analysts welcomed the news but remained skeptical.This case study provides an overview of GoPro, including its historical performances and current strategic initiatives. Readers are asked to assess the organization through the theoretical framework of diffusion of innovations and forecast the short-term and long-term potential of the company.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; GoPro (Firm) -- Case studies; Camera industry -- United States -- Case studies; Wearable video devices -- Case studies